Effects of lifestyle intervention on adults with metabolic associated fatty liver disease: A systematic review and meta-analysis - Chai, Xiao-Ni; Zhou, Bing-Qian; Ning, Ni; Pan, Ting; Xu, Fan; He, Si-Han; Chen, Ni-Ni; Sun, Mei (Frontiers in Endocrinology, 2023)
This systematic review and meta-analysis evaluates the overall effects of lifestyle interventions upon hepatic fat content and metabolism-related indicators among adults with metabolic associated fatty liver disease. It was registered under PROSPERO (CRD42021251527). We searched PubMed, EMBASE, MEDLINE, Cochrane, CINAHL, Scopus, CNKI, Wan-fang, VIP, and CBM from the inception of each database to May 2021 for RCT studies of lifestyle interventions on hepatic fat content and metabolism-related indicators. We used Review Manager 5.3 for meta-analysis and used text and detailed tabular summaries when heterogeneity existed. Thirty-four RCT studies with 2652 participants were included. All participants were obesity, 8% of whom also had diabetes, and none was lean or normal weight. Through subgroup analysis, we found low carbohydrate diet, aerobic training and resistance training significantly improved the level of HFC, TG, HDL, HbA1c, and HOMA-IR. Moreover, low carbohydrate diet is more effective in improving HFC than low fat diet and resistance training is better than aerobic training in reduction in HFC and TG (SMD, -0.25, 95% CI, -0.45 to -0.06; SMD, 0.24, 95% CI, 0.03 to 0.44, respectively). Overall, this is the first review that systematically synthesizes studies focused on the effects of various lifestyle on adults with MAFLD. The data generated in this systematic review were more applicable to obesity MAFLD rather than lean or normal weight MAFLD.